The influence of risk aversion on the entrepreneur’s incubation preferences : a quantitative study - Dias, Pedro Miguel de Carvalho (2020)
Risk is a concept that is intrinsically related with the concept of entrepreneurship. Decisions are taken in context where there is little precedent on the outcomes and conditions. This means that the ability of an individual to manage and the way he perceives and reacts to risk will have an impact on the likelihood of him becoming an entrepreneur and his performance. The purpose of this study is therefore to establish a connection between an individual’s relationship with risk with organizations that aim to help entrepreneurs reduce the risk and potentiate the growth of their ventures: incubation mechanisms. More precisely we look into the perception of value and the willingness to engage with these mechanisms and try to see if these are influenced by an individual’s aversion or propensity to risk. We’ve chosen 4 different incubation mechanisms: Accelerator, Incubator, Venture Capital Firm and Start-up Studio. An online survey was conducted among Entrepreneurs and individuals who are considering starting their business. There were 68 valid responses. With this study we were not able to find a significant difference between the choices of incubators by risk averse and risk propense individuals. Similarly, we were not able to confirm that an individual’s risk aversion is able to significatively predict the amount of equity he/she is disposed to exchange for the support given by different types of incubators. Lastly, our result found that there was no significant difference in risk profile between entrepreneurs who had engaged in start-up competitions and incubation programs and those that didn’t.